Financial literacy and financial education in enginering students of the Technological University of Bolívar based on a gender approach - Cárdenas Escobar, Alba Zulay; Diaz Mendoza, Armando; Hernández Mejía, Sergio; Ortíz Guardo, Juliana Isabel (LACCEI, 2025)
Financial literacy and education are critical in the digital age, given low global knowledge and a persistent gender gap. A key competence, often deficient in engineering students, it is vital for their potential in innovation and technological entrepreneurship. The research measured financial literacy and education in 565 UTB undergrads, with focus on the School of Engineering, Architecture, and Design (219) and gender. Results reveal low financial education: only 12.64% of women in this School had taken a course. In financial literacy, women showed a higher tendency to select "don’t know" and fewer correct answers on key concepts; only 4.30% of the total sample answered all three correctly. Widespread financial knowledge deficit is confirmed at UTB. It is imperative that the School of Engineering, Architecture, and Design urgently integrates inclusive, gender-focused financial education strategies. This is vital to equip future professionals with responsible financial management skills, fostering their well-being and adaptability in the digital market.